Photosynthetic pigments and biomass in noni irrigated with saline waters with and without leaching - Antônio G. L. Souto; Lourival F. Cavalcante; Hans R. Gheyi; Járisson C. Nunes; Francisco I. F. Oliveira; Denizard Oresca (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACTThe response of plants to salt stress is an extremely complex phenomenon that involves morphological, physiological and biochemical changes, modifying the leaf contents of chlorophyll and carotenoids, among others and affecting plant growth, development and production. An experiment was carried out from July 2010 to June 2011, in order to evaluate the contents of chlorophyll a, chlorophyll b, total chlorophyll, carotenoids, the chlorophyll a/b ratio and biomass accumulation of shoots and roots of noni plants, when subjected to irrigation and leaching with water of increasing salinity. The experiment was carried out in a greenhouse, at the Center of Agricultural Sciences of the Federal University of Paraíba, in the municipality of Areia-PB, Brazil. Treatments were distributed in randomized blocks, in a 5 × 2 factorial scheme with four replicates and two plants per plot, and corresponded to levels of electrical conductivity of irrigation water (0.5; 1.5; 3.0; 4.5 and 6.0 dS m-1) in pots with and without leaching. The increase in irrigation water salinity impairs the leaf contents of chlorophyll a, b, total chlorophyll, carotenoids and biomass production of noni plants, but to a lesser extent in all the treatments in which same irrigation water was used for leaching.